Evaluation of fatty acids production by Chlorella minutissima in batch bubble-column photobioreactor - Pereira, Felix M. [UNESP]; Loures, Carla C. A. [UNESP]; Amaral, Mateus S.; Gomes, Fabricio M. [UNESP]; Pedro, Guilherme A.; Machado, Marcela A. G. [UNESP]; Reis, Cristiano E. R.; Silva, Messias B. [UNESP] (Elsevier B.V., 2018)
The environmental problems caused by emissions of greenhouse gases from fossil fuels are increasing the demand for renewable and sustainable energy sources. Biofuels from microalgae, also known as third generation biofuels, promises to be an alternative to substitute the fossil fuels. One of steps to improve the microalgae biofuel production is the optimization of the microalgae production rate. This work applied the Taguchi's method to improve the culture conditions into bubble column photobioreactors in order to maximize biomass and fatty acids productivity by marine microalgae Chlorella minutissima. The independent variables taken into account were carbon dioxide percentage, nitrate concentration, phosphate concentration, supplementation of metals and vitamins, temperature and salinity. The microalgae kinetic growth tacked into account the logistic model. The fatty acids productivity for the best condition was compared with other microalgae cultures in the batch bubble-column photobioreactors presented in literature and the results showed the highest productivity of palmitic acid and a good productivity of stearic acid, important fatty acids to biodiesel formulations. Thus, the methodology and the results presented in this study may be useful for further studies aiming the economic feasibility of microalgae biofuels production.
Keywords: Taguchi; Microalgae; Chlorella minutissima; Photobioreactor; Biofuel